Clinical and laboratory assessment of hormonal and metabolic disorders in experimental animals with alloxan, streptozotocin and dithizone diabetes - Zhautikova, S.B.; Abdikadirova, Kh.R.; Abikenova, F.S.; Talaspekova, Yu.P.; Medvedeva, I.V.; Chergizova, B.T. (Fundamental and Experimental Biology, 2023)
The basic place in experimental diabetology is engaged by chemical models of diabetes. In these patterns, β-cells in pancreatic islet tissue are selectively targeted by diverse agents. Pathogenetic mechanisms of hormonal and metabolic disorders in animals were studied on models of alloxan, streptozotocin and dithizone diabetes. The experiment was carried out on male Wistar rats. Three models of experimental diabetes were created. The groups were equal in terms of observation time (6, 12, 24 months) and number. A complex of laboratory-biochemical methods of lipid and protein metabolism was consumed. Serum enzymes were also determined. The level of glycemia in the studied animals after the introduction of alloxan and streptozotocin ranged from 13.4 to 18.6 mmol/l, glucosuria, polydipsia, polyphagia were observed. A significant (p<0.01) increase in glycemia by 3.10 times, glycated hemoglobin - by 3.16 times, a decrease (p<0.01) of IRI - by 3.76 times and C-peptide - by 2.05 times in animals with streptozotocin diabetes compared with intact animals. Serious lipid metabolism disorders were discovered in alloxan, streptozotocin, and especially dithizone diabetes (24 months of follow-up). This was manifested in a significant (p<0.01) increase in the level of triglycerides - by 1.66 times, atherogenic index (p<0.01) - by 4.43 times and a decrease (p<0.05) in the level of HDL - by 1 43 times compared with the intact CI3 group, as well as an increase in FFA, TCH, LDL, VLDL. In animals with alloxan and dithizone diabetes, the functional activity of the pituitary gland was lessened (the level of growth hormone and CTH (p<0.01), the adrenal cortex and pancreatic α-cells (p<0.01), the activity of the sympathoadrenal system was enlarged, which was reaffirmed by a significant (p<0.01) by an increase in the level of adrenaline, noradrenaline - by 1.42 times. An above pronounced suppression of the endocrine glands was observed in animals with streptozotocin diabetes.